2014
DOI: 10.11108/kagis.2014.17.2.059
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution Analysis of One-Person Household - The Case of Busan City -

Abstract: At present, Korean one-person households have been continuously increased in 2014년 3월 8일 접수

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…An analysis of the capital area (Choi and Yoon 2013) finds that the elderly population mainly lives in self-owned detached houses and houses that have been built for more than 20 years, typically in the outskirts of the capital area. A study of Busan (Yoo and Nam 2014) showed that elderly single-person households live in small houses or old residential areas in the old city center area. In a study on Cheongju, the elderly residential area is relatively far from convenient areas where public facilities are concentrated (Jeon et al 2019).…”
Section: Introduction Theoretical Background and Purpose Of The Studymentioning
confidence: 99%
“…An analysis of the capital area (Choi and Yoon 2013) finds that the elderly population mainly lives in self-owned detached houses and houses that have been built for more than 20 years, typically in the outskirts of the capital area. A study of Busan (Yoo and Nam 2014) showed that elderly single-person households live in small houses or old residential areas in the old city center area. In a study on Cheongju, the elderly residential area is relatively far from convenient areas where public facilities are concentrated (Jeon et al 2019).…”
Section: Introduction Theoretical Background and Purpose Of The Studymentioning
confidence: 99%